ANALYSIS OF THE EFFECT OF FIRM SIZE, CAPITAL STRUCTURE, FIRM GROWTH AND FINANCIAL PERFORMANCE ON FIRM VALUE IN MANUFACTURING COMPANIES LISTED IN INDONESIA STOCK EXCHANGE - saragih, jhon raphael (International Journal of Public Budgeting, Accounting and Finance, 2019)
The objectives of this study is to analyse the effect of Firm Size, Capital Structure, Firm Growth and Financial Performance simultaneously and partially influence the Firm Value on Manufacturing Companies Listed on the Indonesia Stock Exchange (IDX) for the 2014-2017 Period. The type of research is causal associative research which is useful for analysing the causal relationship between one variable with other variables using quantitative data types. This study used secondary data which obtained from IDX and from other official site sources. The population in this study are all manufacturing companies listed in Indonesia Stock Exchange for the period 2014-2017 which informs the phased financial statements contained in the firm's annual report. The total population in this study amounted to 147 companies, with a sample of 53 companies using purposive sampling method, the number of observations was 212 observation units. The data collection method used is documentation technique. The method of data analysis in this study is multiple linear regression and path analysis with the help of Statistical Product and Service Solutions (SPSS) software. The results showed that the size of the firm has a positive and significant effect on firm value, capital structure has a positive and significant effect on firm value, financial performance has a positive and significant effect on firm value while firm growth has a negative and significant effect on firm value.